The impact of formality, integration, and commitment on the performance of Latino-owned small businesses - Sterling A. Starbird; Jill M. Martin; Yacanex Posadas; Alma Gutiérrez (Administrative Sciences, 2022)
Supporting the growth of minority-owned small- and medium-sized enterprises (SMEs) is an important goal in many countries. In the US, Latinos start businesses faster than any other demographic group, yet Latino wealth and income have not kept pace with the broader society. In this study, we explore the impact of different business and owner characteristics on the performance of Latino-owned small businesses. Using a survey of over 200 Latino small business owners in Silicon Valley, we apply ordered logistic regression to measure the effect of several variables on firm revenue. Our findings suggest that in addition to the gender and education of the owner, the most important factors impacting business performance are the owner's commitment to the business, formal registration of the business, and the degree to which the business is integrated into the broader business community. This research adds to our understanding of the factors that significantly impact the economic success of Latino-owned small businesses. The results will be helpful to organizations that support the development and sustainability of Latino entrepreneurship.
Keywords: 350; SMEs; critical success factors; ethnic entrepreneurship; Latino entrepreneurship; small business